Screening of fungi for diesel biodegradation in liquid medium / Hanieh Mofidi - Hanieh , Mofidi (2019)
Diesel is one of the common petroleum hydrocarbon (PH) components that cause water pollution. Being as the recalcitrant pollutant, its treatment requires extensive processes which pose physically and financially challenges. Bioremediation using fungi is the emergence method that offer the solution to such challenges. This study explore the use of fungi for diesel biodegradation in liquid media. Twelve potential fungal strains have been isolated from contaminated and undisturbed soils using diesel coated agar media. Each fungal strain was further tested for their tolerance based its growth within the duration of seven days using 1% and 10% diesel concentrations (v/v) in potato dextrose broth media by the shake flask method. Five prospect fungi had been regarded to have high diesel tolerance. Simple identification method showed that they belong to the division of Ascomycota, and namely as, Penicillium sp. A, Penicillium sp. B, Penicillium sp. C, Aureobasidium sp. and Aspergillus sp. Later, the ability to degrade diesel for all five strains were assessed using redox indicator and gas chromatography mass spectrometry (GC/MS) analysis. Both assessments confirmed that all prospect fungal have the expected ability. Meanwhile, GC/MS analysis for the diesel concentration of 1% (v/v) have further narrowed down to two isolates of Penicillium sp.A and Aspergillus sp. which are to be the good diesel degrader, 70% to 90%, respectively. The rest of other isolates did not show to be a good prospect of fungi. One strain (Aureobasidium sp.) did not represent a good formation of biomass floc (colloidal) with the other two strains had low degradation (< 60%). However, at the diesel concentration of 10% (v/v), Penicillium sp.A is a better performer, when it removed almost 70% of diesel, compared to 63% removal for Aspergillus sp.. Final assessment was done using a higher concentration of biomass (9 g/l) with continuous stirred tank reactor. Unexpectedly, both isolates have shown the declining of diesel reduction where, Aspergillus sp. reduced 41% and Penicillium sp.A of 77%. Nevertheless, the final assessment did not take account of factors of evaporation and headspace which may affect the overall diesel degradation assessment in a closed vessel.